Impact of positive and negative corporate social responsibility on automotive firms' financial performance: A market‐based asset perspective. (4th March 2020) - Lin, Woon Leong; Ho, Jo Ann; Lee, Chin; Ng, Siew Imm
Abstract: Prevailing studies on the economic implication of corporate social responsibility (CSR) for businesses has mainly stressed on the positive facet of corporate social responsibility (PCSR), failing to comprehend that firms also espouse behaviors and initiatives which can be characterized as negative corporate social responsibility (NCSR). Additionally, limited researches have considered how both PCSR and NCSR influence corporate financial performance (CFP). In consideration of this view, we present a framework that connects both PCSR as well as NCSR to CFP. We also analyzed the moderating role of the firm's market‐based asset. Using 924 observations from 2011 to 2017 and a combined secondary data of 132 global automotive firms from CSRHub and Thomson Reuters Datastream, we examined how increases in either PCSR or NCSR relate to CFP via dynamic panel data system Generalise Moment of Method estimates. Our results demonstrate that PCSR improves CFP while and NCSR is detrimental to a firm's financial performance. Correspondingly, the results indicate that market‐based asset moderates the relationship between PCSR and NCSR. Firms that possess higher market‐based assets tend to enjoy higher profitability with PCSR as they are in a better position. However, it has been observed that market‐based assets tend to weaken the relationship between CFP and NCSR.